Situational Leadership Style of Regional Finance and Assets Agency in the Office of the Governor of South Sulawesi - Yusuf, Ayu Ahsari; Niswaty, Risma; Arhas, Sitti Hardiyanti (ASHA Publishing, 2024)
This study aims to find out about the overview of the implementation in the implementation of the situational leadership style of the Regional Finance and Assets Agency in the Office of the Governor of South Sulawesi. This research is qualitative, therefore, to achieve the research objectives, data collection techniques are used, namely observation, interviews and documentation. There are 5 informants, namely employees of the Regional Finance and Assets Agency. Based on the results of this study, the implementation of situational leadership style in the application of regional financial and asset agencies in the South Sulawesi Governor's Office has been successfully implemented. This can be seen from several things, such as providing direction in the implementation of work activities, inspiring subordinates to be innovative in completing tasks, and providing solutions for subordinates who experience an inability to work productively. Furthermore, there are indicators in supporting this leadership style, such as providing space for subordinates to voice their opinions, providing the necessary support, and providing motivation so that the performance of subordinates is getting better. In addition, the indicator involves subordinates in decision-making, listens to their ideas and ideas, and involves them in the decision-making process. This leadership style also involves the indicator of delegating authority to subordinates and giving them the freedom to express their opinions